HIV-1 drug resistance mutations detection and HIV-1 subtype G report by using next-generation sequencing platform. (September 2020) - Gholami, Mohammad; Rouzbahani, NeginHosseini; Samiee, SiamakMirab; Tayeri, Katayoun; Ghorban, Khodayar; Dehkharghani, Alireza Dolatyar; Gholami, Ali Akbar; Moshiri, Farzaneh; Sattari, Arash; Dadmanesh, Maryam; Mohraz, Minoo
Abstract: Background: Based on world health organization (WHO) recommend, drug resistance assay should be performed in initial of treatment and after treatment for administering and monitoring of anti-retroviral regime in HIV-1 infected patients. Material and method: NGS analyses were performed on forty-one plasma samples from HIV-1 affected patients using the Sentosa SQ HIV genotyping assay (Vela-Diagnostics, Germany). This system comprises a semi-automated Ion torrent based platform and the sequencing results were analyzed based on ANRS, REGA and Stanford drug resistance algorithms. Phylogenetic analysis was analyzed based on https://comet.lih.lu database as well as MEGA5 Software. Results: Drug resistances were identified in thirty-three samples (80%) out of forty-one samples. The Phylogenetic analysis results showed that CRF-35AD (94%) and subtypes B (2.4%) and G (2.4%) were dominant subtypes in this study. NRTI and NNRTI associated dominant mutations were M184I/V and K103 N.High-level resistance to lamivudine (3 TC) and Emtricitabine (FTC) were detected in 34.3% of patients while 53.1% were resistant to Efavirenz (EFV) and Nevirapine (NVP). The Protease inhibitor (PI) minor and major mutations were not reported but more than 95% of samples had polymorphisms mutation in K20R, M36I, H69K, L89 M positions. These mutations are subtype dependent and completely are absent in subtype B virus. The secondary mutations were reported in positions of E157Q, S230 N, and T97A of integrase gene and four samples represent low-level resistance to integrase strand transfer inhibitor (INSTI). Conclusions: This is the first preliminary evaluation of HIV-1 drug resistance mutation (DRM) by using the Sentosa SQ HIV Genotyping Assay in Iran. The NGS represent a promising tool for the accurate detection of DRMs of CRF-35AD that is dominant subtype in Iranian HIV-1 infected population and for the first time revealed HIV-1 subtype G in Iranian population. In the present study polymorphic mutation in the position of K20R, M36I, H69K, L89 M were properly reported in CRF35AD that is dominant in Iranian HIV patients. Highlights: The preliminary HIV-1 drug resistance by using the NGS method in Iran.